2017
DOI: 10.1016/j.nbd.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The blood-brain barrier in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder characterized by the pathological accumulation of amyloid beta (Aβ) peptides and neurofibrillary tangles containing hyperphosphorylated neuronal tau protein. AD pathology is also characterized by chronic brain inflammation, which promotes disease pathogenesis. In this context, the blood-brain barrier (BBB), a highly specialized endothelial cell membrane that lines cerebral microvessels, represents the interface between neural cells and circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
501
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(512 citation statements)
references
References 267 publications
(369 reference statements)
1
501
1
9
Order By: Relevance
“…Indeed, AD is associated with microvascular dysfunction, altered protein expression in particular Aβ transporters, LRP1 and RAGE, by endothelial cells and defective BBB that impact Aβ clearance (Zlokovic, ). Although the underlying mechanisms involved in BBB dysfunction are complex, oxidative stress and diverse inflammatory mediators seem to play a role (Zenaro, Piacentino, & Constantin, ). In this context, boldine treatment could improve BBB function by its protective action on endothelial cells and, as a consequence, could ameliorate Aβ clearance and reduce Aβ accumulation in boldine treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AD is associated with microvascular dysfunction, altered protein expression in particular Aβ transporters, LRP1 and RAGE, by endothelial cells and defective BBB that impact Aβ clearance (Zlokovic, ). Although the underlying mechanisms involved in BBB dysfunction are complex, oxidative stress and diverse inflammatory mediators seem to play a role (Zenaro, Piacentino, & Constantin, ). In this context, boldine treatment could improve BBB function by its protective action on endothelial cells and, as a consequence, could ameliorate Aβ clearance and reduce Aβ accumulation in boldine treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral immune cells such as monocytes and lymphocytes that are normally low in the parenchyma have increased numbers in the brains of AD patients and animal models (Zenaro et al . ). BBB disruption can stem from several possible events associated with AD.…”
Section: Role Of Rocks: Vascular Pathologies and Vascular Risk Factormentioning
confidence: 97%
“…Importantly, such damage may result from the presence of prolonged systemic inflammation and elevated levels of PICs, which increase the permeability of tight junctions by decreasing levels of glycocalyx and other adhesion molecules, as well as causing endothelial cell damage and disruption of the of glia limitans [385,386]. It is important to note that such damage may result from PICs in the systemic circulation or following activation of microglia and astrocytes in the brain and the latter phenomenon goes some way to explaining the dysfunction of the neurovascular unit seen in early AD patients described above [382,385,386].…”
Section: The Function Of the Bbb In This Modelmentioning
confidence: 96%
“…Several authors have reported reduced expression of adhesion molecules and tight junction proteins in BBB endothelial cells combined with a dysfunctional and/or disrupted neurovascular unit in AD patients with early disease long before the occurrence of dementia and in the absence of neurodegeneration and brain atrophy [382][383][384]. Importantly, such damage may result from the presence of prolonged systemic inflammation and elevated levels of PICs, which increase the permeability of tight junctions by decreasing levels of glycocalyx and other adhesion molecules, as well as causing endothelial cell damage and disruption of the of glia limitans [385,386].…”
Section: The Function Of the Bbb In This Modelmentioning
confidence: 99%